Diminishing calendar anomalies: case of Indian equity markets. (28th October 2020) - Saxena, Sakshi; Purohit, Harsh; Malhotra, Nidhi
The present study probes the presence of seasonal anomaly mainly day of the week effect and month of the year effect in the Indian Stock Market ranging from January 2011 till January 2018. Daily and weekly closing data of Nifty Financial services index, Nifty Auto index, Nifty Bank index and Nifty 50 index has been considered for the same. Regression model using dummy variables has been used to investigate the same. The results states that none of the four nifty indices shows day of the week effect. Nifty 50 does not indicate the presence of the month of the year effect. In contrast, April effect is present in Nifty Auto. Nifty Bank index shows February and August effect, while Nifty Financial Services shows February effect.